Effect of polyethylene glycol and nano clay on swelling, diffusion, network parameters and drug release behavior of interpenetrating network copolymer. Issue 8 (22nd September 2021) - Samanta, Himadri Sekhar; Ray, Samit Kumar
Abstract: Controlled release of a drug from a biocompatible nontoxic polymer at a predetermined rate by maintaining a constant drug level for a specific time period causes its maximum utility with reduced side effect and more efficient cure of the disease. Accordingly, several composite hydrogels were synthesized by free radical crosslink copolymerization of acrylic acid (AA), acrylamide (AM), and N'N‐methylene bis acrylamide (MBA, crosslinker) in water in the presence of varied amounts of polyethylene glycol (PEG) and nano sized sodium montmorillonite (NaMMT) clay. The structures of the hydrogels were characterized. The effect of the synthesis and process parameters on the swelling, diffusion, network parameters, and drug release properties of the polymer networks were studied. The hydrogel containing 3.2 wt% NaMMT clay and 24 wt% PEG showed the best equilibrium swelling ratio (33.2 g/g), drug entrapment efficiency (86%), and drug release properties (96.6% in 30 h at pH of 7.4) for a model drug riboflavin. The results indicate a significant improvement of swelling and drug release properties of the polymer in the presence of PEG and NaMMT clay in the gel network. Abstract :